(untitled) (LACCEI, 2024)
Currently in Ecuador, one of the biggest problems in terms of the road system is the condition and maintenance of roads, where the consequences of these imperfections for the population are notorious. The objective of this project is to develop a mortar based on sugar cane bagasse ash for the repair of roads through the characterization of different materials, the design of dosages and the development of optimized mixtures with additions of ash and zeolite. Due to the situation the country is going through, the opportunity arises to propose a repair mortar that contributes with sustainable and technical criteria. In order to meet the mentioned objectives, it was necessary to carry out tests on different materials, which allowed the design of the traditional mortar mixes M3, M5 and, in turn, of the dosages M - 50% C and M - 75% C, with variations in the percentage of ash addition in replacement of sand. The execution of compression, traction and adherence tests allowed evaluating the properties of each mixture and dosage, where maximum values of compressive strength of 17.96 MPa, modulus of elasticity of 2000 Kgf/cm2 and adherence of 0.52 MPa were determined. The M5 - 50% C mix, which is postulated under different criteria as a proposed repair material due to its better performance among the options evaluated, does not meet the parameters required by the regulations for rigid pavement repair mortars.